PGE2/EP4 Signaling Controls the Transfer of the Mammary Stem Cell State by Lipid Rafts in Extracellular Vesicles. (16th September 2016) - Lin, Meng-Chieh; Chen, Shih-Yin; Tsai, Ho-Min; He, Pei-Lin; Lin, Yen-Chun; Herschman, Harvey; Li, Hua-Jung
Abstract : Prostaglandin E2 (PGE2 )-initiated signaling contributes to stem cell homeostasis and regeneration. However, it is unclear how PGE2 signaling controls cell stemness. This study identifies a previously unknown mechanism by which PGE2 /prostaglandin E receptor 4 (EP4 ) signaling regulates multiple signaling pathways (e.g., PI3K/Akt signaling, TGFβ signaling, Wnt signaling, EGFR signaling) which maintain the basal mammary stem cell phenotype. A shift of basal mammary epithelial stem cells (MaSCs) from a mesenchymal/stem cell state to a non-basal-MaSC state occurs in response to prostaglandin E receptor 4 (EP4 ) antagonism. EP4 antagonists elicit release of signaling components, by controlling their trafficking into extracellular vesicles/exosomes in a lipid raft/caveolae-dependent manner. Consequently, EP4 antagonism indirectly inactivates, through induced extracellular vesicle/exosome release, pathways required for mammary epithelial stem cell homeostasis, e.g. canonical/noncanonical Wnt, TGFβ and PI3K/Akt pathways. EP4 antagonism causes signaling receptors and signaling components to shift from non-lipid raft fractions to lipid raft fractions, and to then be released in EP4 antagonist-induced extracellular vesicles/exosomes, resulting in the loss of the stem cell state by mammary epithelial stem cells. In contrast, luminal mammary epithelial cells can acquire basal stem cell properties following ingestion of EP4 antagonist-induced stem cell extracellular vesicles/exosomes, and can then form mammary glands. These findings demonstrate that PGE2 /EP4 signaling controls homeostasis of mammary epithelial stem cells through regulating extracellular vesicle/exosome release. Reprogramming of mammary epithelial cells can result from EP4 -mediated stem cell property transfer by extracellular vesicles/exosomes containing caveolae-associated proteins, between mammary basal and luminal epithelial cells.